Purification and dose-dependent toxicity study of abrin in swiss albino male mice - Chaturvedi, K; Jadhav, S E; Bhutia, Y D; Kumar, O; Kaul, R K; Shrivastava, N (Cellular and Molecular Biology, 2015)
Abrin, a phytotoxin obtained from the seeds of the Abrus precatorius plant, is highly toxic with an estimated human fatal dose of 0.1-1 µg/kg. In this study, abrin was purified and characterized through SDS PAGE and mass spectrometry analysis; further study on toxicity was carried out to investigate the alteration in biochemical, and hematological variables through histopathological observations in mice. The intraperitoneal LD50 value of purified abrin for mice was found to be 0.91µg/kg of body weight. Mice were exposed to 0.4 and 1.0 LD50 abrin doses intraperitoneally and observed on days 1, 3, and 7. Plasma GOT and GPT levels increased significantly at both doses. At 1.0 LD50 dose, alkaline phosphatase, bilirubin, urea, uric acid, and creatinine levels increased, whereas albumin, total protein, glucose and cholesterol levels decreased significantly. Abrin intoxication also altered the hemoglobin, WBC, and RBC counts significantly at 1.0 LD50 dose. Liver GSH levels decreased while lipid peroxidation increased significantly in a dose-dependent manner. Biochemical changes were supported by the histological investigation, which also showed the degenerative changes in organs. In conclusion, abrin intoxication caused toxic effects and severe damages on studied organs mediated through alteration in biochemical and hematological variables, lipid peroxidation, and degeneration.